PENGARUH METODE BERCERITA TERHADAP PENDIDIKAN AKHLAK ANAK USIA DINI DI PAUD LITTLE RAINBOW BALIKPAPAN - Sulpa; Iskandar Yusuf (STKIP Subang, 2026)
This study aims to analyze the influence of the storytelling method on the moral education (akhlak) of early childhood students at PAUD Little Rainbow Balikpapan. Storytelling is considered suitable for early childhood learners because it delivers moral messages through characters and plot in an enjoyable and easily understood way. This research used a quantitative correlational approach involving 8 respondents. Data were collected through Likert-scale questionnaires for the storytelling method variable (X) and the moral education variable (Y), then analyzed using validity testing, normality testing, simple linear regression, and Pearson product moment correlation with the aid of SPSS. The results showed that all 20 items of the instrument, 10 items of the storytelling method variable and 10 items of the moral education variable, were valid. The regression analysis produced the equation Y = 2.407 + 0.920X with a significance value of 0.000, and the correlation coefficient reached 0.998, categorized as very strong, with a coefficient of determination of 99.6%. These findings indicate that the storytelling method has a positive and significant influence on early childhood moral education, so teachers are encouraged to continue optimizing storytelling activities as a primary strategy for early childhood moral education.